In vitro evaluation of 2-methoxyestradiol-bis-sulphamate and crude Sutherlandia frutescens extracts as possible anticancer agents - Joubert, Annie M. (University of Pretoria, 2014)
Dissertation (MSc (Physiology))--University of Pretoria, 2013.